Ab initio electronic structure calculations for point defects in CoAl and CoGa - N. Stefanou; R. Zeller; P.H. Dederichs (Physical Review B, 1987)
Self-consistent, first-principles calculations are presented for the electronic structure of some point defects in the binary alloys CoAl and CoGa. All possible structural defects-i.e., antistructure atoms and vacancies-as well as 3d transition-metal impurities on both sublattices are considered. The calculations are based on the Korringa-Kohn-Rostoker Green's-function method and on density-functional theory in the local-spin-density approximation. The calculated densities of states, charge transfers, and magnetic moments are discussed and compared with the results of other theoretical calculations and the available experimental data.